Guidance and Counseling Service Nigerian University System: Problems and Way Forward - Adanna, Chinwuba Mary; Agerewe, Samuel Benjamin; Rita, Kozah Bitrus (International Journal on Integrated Education, 2023)
This paper examined the problems that has militated against effective Guidance and Counseling service in the universities in Nigeria. Secondary data were used in the paper. The secondary data were gathered from print materials and online publications. The paper specifically stated that poor funding, inadequate Guidance and Counseling materials, shortage of trained Guidance and Counsellors, poor capacity building programme, negative attitude of university community and inadequate infrastructure facilities are problems that have hindered effective Guidance and Counselling services delivery in the universities in Nigeria. Based on these problems, the paper recommended that; Universities management should increase the budgetary allocation of Guidance and Counseling units in the various universities. Counselling materials like psychological tests, play gadget, tape recorder, log book, record folder, etc should be provided for the guidance and career development centres for effective service delivery. University authorities should employ more qualified/trained Guidance and Counsellors and post them to the Guidance and counseling units.